Acesso à saúde contemporâneo no Brasil e em Portugal como um direito social - dos Santos Gomes , Priscilla (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Access to health care is a social law whose inspiration the value of equality among all human beings and in this sense the Brazilian and Portuguese public policies have measured recent efforts to meet social demands. The right to health is part of a set of so-called rights of social rights, related to the principles of human dignity, equality and solidarity, aimed at achieving social justice. In Brazil, the conquest of the Unified Health System - SUS, in 1988, was the main achievement of contemporary public health policy that meets citizens. In Portugal the creation of the National Health Service - SNS regulated in Decree Law No. 56 of August 26, 1979, allowed new models of access to people’s health. In both countries, access to health requires permanent political actions of the state, which is why the right to health is still very uneven